Electromechanical properties of fine-grain, 0.7 Pb(Mg(1/3)Nb(2/3))O3-0.3PbTiO3 ceramics - Wang, Haifeng (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2004)
A fine grain, relaxor-based piezoelectric ceramic 0.7 Pb(Mg(1/3)Nb(2/3))O3-0.3PbTiO3 (PMN-30% PT) has been investigated, which was fabricated using the columbite precursor method. The complete set of electromechanical properties of the piezoceramic at room temperature is determined using a combination of ultrasonic and resonance techniques. This fine-grain ceramic (grain size < or = 2.5 microm) exhibits ultra-high dielectric permittivity (epsilon33(T)/epsilon0 approximately 7000) and a high coupling coefficient k(33) (= 0.78). Ultrasonic spectroscopy was used to measure the dispersion of the phase velocity and attenuation for the longitudinal wave propagating in the poling direction. Lower attenuation and smaller velocity dispersion were observed compared to modified Pb(Zr(x)Ti(1-x)O3 (PZT-5H) ceramics. The measurement results show that this fine-grain PMN-30% PT ceramic is a very good material for making ultrasonic array transducers